2017
DOI: 10.14341/dm9291
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of wound healing in patients with neuropatic diabetic foot ulcers

Abstract: ФГБУ Национальный медицинский исследовательский центр эндокринологии Минздрава России, Москва ОБОСНОВАНИЕ. Процессы заживления ран нижних конечностей замедлены при сахарном диабете (СД). В различных ис-следованиях показана роль контроля диабета, цитокинов и факторов роста в этих процессах. Однако роль генов, определя-ющих пролиферацию клеток, синтез коллагена, формирование здоровой грануляционной ткани, остается малоизученной. ЦЕЛЬ.Изучить особенности экспрессии генов коллагенов на различных фазах раневого про… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…We found 12 RCTs 24,[38][39][40][41][42][43][44][45][46][47][48] comprising 986 participants comparing collagen/alginate dressings to a standard of care and which fulfilled our inclusion criteria. None of the studies were double-blind; three 38,39,41 were outcome blind, one 44 patient blind, and one had uncertain blinding.…”
Section: Collagen or Alginatesmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 12 RCTs 24,[38][39][40][41][42][43][44][45][46][47][48] comprising 986 participants comparing collagen/alginate dressings to a standard of care and which fulfilled our inclusion criteria. None of the studies were double-blind; three 38,39,41 were outcome blind, one 44 patient blind, and one had uncertain blinding.…”
Section: Collagen or Alginatesmentioning
confidence: 99%
“…Eleven studies reported on reduction in ulcer area. 24,[39][40][41][42][43][44][45][46][47][48] Only two 41,46 reported this being significantly improved in the intervention arm compared to a control dressing. The former was performed in a primarily inpatient population, and, as outcomes were assessed at only 9 days, generalisability is limited.…”
Section: Outcome: Reduction In Ulcer Areamentioning
confidence: 99%
See 1 more Smart Citation
“…All were at moderate or high risk of bias and most were non-blinded. Four studies compared collagen only with moist wound therapy, 45,47,48,52 one study 46 used collagen-alginate, one used a calcium alginate, 51 one compared a collagen/oxidised regenerated cellulose/silver treatment with foam, 29 one the same collagen/oxidised regenerated cellulose but without silver, 54 one compared collagen with negative pressure wound therapy, 50 one compared collagen with gauze or hydrocolloid dressings 49 , and another two 51,53 alginate alone as the intervention. Of the 12 studies, nine of them 29,[45][46][47]49,[51][52][53][54] did not report a difference in wound healing or reduction in ulcer area at the end of study duration.…”
Section: Honey or Bee Productsmentioning
confidence: 99%
“…241 Overall, the balance of effects was not thought to favour either Rationale: We identified 19 studies which fulfiled our inclusion criteria. 50,152,[244][245][246][247][248][249][250][251][252][253][254][255][256][257][258][259][260] All studies were thought to be at moderate to high risk of bias.…”
Section: Rationalementioning
confidence: 99%